Fabrication of microfiber loop resonator-based comb filter - Lim, Kok Sing; Harun, Sulaiman Wadi; Jasim, Ali Abdulhadi; Ahmad, Harith (John Wiley & Sons, 2011)
Microfiber loop resonator (MLR) is fabricated by coiling of a microfiber, which was obtained by the fast stretching of a heated single mode fiber. The MLR is embedded in low refractive index material to keep the system robust. Two comb filters with a constant spacing of 0.16 nm and 0.71 nm are successfully achieved, which the extinction ratio can be adjusted by controlling the state of polarization of the input light. It was also found that the wavelength of each peak and the spacing remain unchanged regardless of the state of polarization of the input light. This MLR does not have major issues with input-output coupling and presents a completely integrated fiberized solution.